2022
DOI: 10.26717/bjstr.2022.42.006742
|View full text |Cite
|
Sign up to set email alerts
|

"Cations as Molecular Switches for Junctional Adhesion Molecule-A"

Abstract: Junctional adhesion molecules (JAMs) are key structural and functional cell adhesion components of tight junctions (TJs). Cadherins (CADs), in the AJ and JAM-A in the TJ are calcium-dependent adhesion molecules. The expression of JAM-A in cells exposed to different ionic microenvironments led us to hypothesize that other cations may play a role in its function. A cation-binding site algorithm was used to identified calcium, copper, iron, magnesium, and zinc potential binding sites in JAM-A. In this article, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…Because rJAMA was already aggregated beyond the SEC sensitivity we could not confirm the effects of Zinc. JAMA's susceptibility to Zinc was reported by our group previously [37]. Using ZetaView we have confirmed that rJAMA is not dependent on Zinc.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Because rJAMA was already aggregated beyond the SEC sensitivity we could not confirm the effects of Zinc. JAMA's susceptibility to Zinc was reported by our group previously [37]. Using ZetaView we have confirmed that rJAMA is not dependent on Zinc.…”
Section: Discussionsupporting
confidence: 84%
“…Figure 5A demonstrates through SEC profiles how JAMA and rJAMA soluble domains behave in solution. JAMA is expected to behave mostly as a monomer in the absence of environmental factors present at the tight junction where it can form dimers and other levels of aggregation [36][37][38]. Examining the SEC profiles in Figure 5A, we observe a contrast between monomeric JAMA and multimeric rJAMA.…”
Section: Protein Sequences and Plasmidsmentioning
confidence: 90%
See 1 more Smart Citation